Imam Al Ghazali Ideal Education Curriculum - Islakhul Anam; Abdul Fatah (RedWhite Press, 2021)
Based on the implementation, the curriculum is divided into ideal curriculum and real curriculum. The ideal curriculum is a curriculum that is conceptual and contained in official documents. The implementation of this ideal curriculum is called the real curriculum. Good curriculum implementation is determined by good planning. Therefore, this paper attempts to describe the ideal educational curriculum from the perspective of Imam Al Ghazali. According to Al Ghazali himself, there needs to be a dualism of values in the ideal curriculum which includes both material and spiritual aspects. This is also in line with what is expected by the national education goals.